Conservative non-surgical endodontic management of a large cyst-like periapical tunnel lesion with 22-month CBCT follow-up: A case report - ROHILLA, Smriti; MAKKAR, Sameer; GUPTA, Sandeep (International Arab Journal of Dentistry (IAJD), 2025)
The present case report epitomises the successful non-surgical management of a large cyst-like periapical tunnel lesion of endodontic origin due to trauma using the Lesion Sterilization and Tissue Repair technique. Endodontic orthograde treatment (and re-treatment) was performed in association with triple antibiotic paste as an intra-canal medication in a sixteen-year-old boy. Preoperative CBCT, as well as the 22-month CBCT follow-up, were used to compare the evolution of the healing of the lesion. Accurate diagnosis in combination with non-surgical orthograde endodontic treatment can lead to complete healing of large lesions without any need for surgical intervention.